2020
DOI: 10.18182/tjf.684387
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oil heat treatment on oil uptake, density and moisture content in brutian pine (Pinus brutia Ten.) wood

Abstract: Sıcak-soğuk biyo-yağ işleminin yerli çam türü ağaç malzemenin özellikleri üzerine etkileri bilinmemektedir. Bu çalışmada sıcak-soğuk biyo-yağ işleminin kızılçam odunundan hazırlanan ağaç malzemede yağ alımı, yoğunluk ve rutubet miktarı üzerine etkisinin belirlenmesi amaçlanmıştır. Çalışmada, hint yağı (Ricinus communis L.), keten yağı (Oleum linii), karma yağ (hint yağı + keten yağı) ve kızılçam (Pinus brutia Ten.) diri odunu kullanılmıştır. Odun örnekleri 6 saat sıcak (110 ºC ± 2 ºC) yağ ile muamele edildikte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Dubey et al (2016) revealed that the density of Pinus radiata wood after heat treatment with oil was at a higher level than the untreated control group. In the results found from our study, our results were compatible to the results obtained by Var and Demir (2020) and Dubey et al (2016), as the oil heat-treated samples gave higher oven-dry density values than the control samples.…”
Section: Oven-dry Density Testsupporting
confidence: 93%
See 2 more Smart Citations
“…Dubey et al (2016) revealed that the density of Pinus radiata wood after heat treatment with oil was at a higher level than the untreated control group. In the results found from our study, our results were compatible to the results obtained by Var and Demir (2020) and Dubey et al (2016), as the oil heat-treated samples gave higher oven-dry density values than the control samples.…”
Section: Oven-dry Density Testsupporting
confidence: 93%
“…According to their results, the density of the test samples increased by 40.38%-78.85% compared to the control. In the results obtained from our study, our results were compatible to the results obtained by Bayraktar and Pelit (2022) and, Var and Demir (2020), as the oil heat-treated samples gave higher oven-dry density values than the control samples. During all water uptake periods, control samples absorbed more water than the samples treated with corn oil.…”
Section: Air-dry Density Testsupporting
confidence: 92%
See 1 more Smart Citation